Interactive e-module based on PQ4R on e-learning platform to improve conceptual understanding of 12th grade students - Rahadi, I Wayan Selamet; Astawa, I Wayan Puja; Suweken, Gede (Indonesian Journal of Educational Development (IJED), 2025)
Based on an analysis conducted at the senior high school level, it was found that several students were still unable to grasp mathematical concepts effectively. One contributing factor to this issue was the lack of engaging and interactive instructional media. This study aimed to develop e-learning as a medium for mathematics instruction to improve concept comprehension among twelfth-grade students. This research followed a design-based approach using the Plomp model, which consisted of three stages: the preliminary research stage, the development stage, and the assessment stage. The subjects of the study were 12th-grade students from SMA Negeri 1 Ubud. The instruments used in this study included product validation instruments, practicality instruments, teacher and student questionnaires, as well as effectiveness instruments in the form of pre-tests and post-tests. The characteristics of the developed product included interactivity, a systematically structured learning management system, and the ability to facilitate both teachers and students in accessing learning materials and outcomes within a well-integrated system. The results indicate that the developed e-learning media is valid, practical, and effective. Further research is recommended to add Artificial Intelligence (AI) integration so that the content is more extensive.